2022
DOI: 10.3390/joitmc8030148
|View full text |Cite
|
Sign up to set email alerts
|

Research Productivity for Augmenting the Innovation Potential of Higher Education Institutions: An Interpretive Structural Modeling Approach and MICMAC Analysis

Abstract: Current literature merely identifies the driving factors of research productivity in higher education institutions without directly examining their interrelationships that would offer some fundamental insights into the nature of these factors. Thus, this work intends to identify those driving factors and establish their structural relationships to determine those factors with crucial roles in advancing research productivity. Due to the subjectivity of the identified driving factors and the notion that the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 147 publications
0
19
0
1
Order By: Relevance
“…Regrettably, to the best of researchers' knowledge, this relationship is unexplored in developing countries such as Tanzania. Given the fact that research as an activity is considered inherently creative and innovative (Ocampo et al, 2022;Callaghan, 2014), it demands one to be more creative and innovative in bringing up new ideas and developing them into a form that can be disseminated to others. Thus, it can be assumed that, academics with higher levels of openness to change are more likely to be productive in research publication.…”
Section: Openness To Change and Research Publicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Regrettably, to the best of researchers' knowledge, this relationship is unexplored in developing countries such as Tanzania. Given the fact that research as an activity is considered inherently creative and innovative (Ocampo et al, 2022;Callaghan, 2014), it demands one to be more creative and innovative in bringing up new ideas and developing them into a form that can be disseminated to others. Thus, it can be assumed that, academics with higher levels of openness to change are more likely to be productive in research publication.…”
Section: Openness To Change and Research Publicationmentioning
confidence: 99%
“…Worldwide, research publication has a significant role to both academics as well as higher education institutions (HEI) (Ocampo et al, 2022). For academics, publication outputs affect their advancement and reputation in academia (Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, despite having studies that explored RSE and research productivity (RPR) in higher education, a number of these studies have been conducted in developed countries, there is dearth of research in the context of developing countries, in particular Tanzania. Besides, previous studies, however, have produced inconsistent results, leading to the conclusion that RSE and RPR relationship is inconclusive (Ocampo et al, 2022;Zhang, 2022;Hemmings and Kay, 2009;Pasupathy and Siwatu, 2014). However, given the fact that self-efficacy results from a relationship between personal characteristics, behavior patterns and environmental factors (Wood and Bandura, 1989) the differences in institutional working environments may limit the relevance of the results obtained.…”
Section: Introductionmentioning
confidence: 97%
“…Prior research demonstrated a positive influence of RSE on research related outcomes in higher education (Adekunle, 2022;Gaoat, 2022;Ocampo et al, 2022;Zhang, 2022;Garnasih et al, 2017;Hemmings and Kay, 2009). Academics with higher levels of RSE are more likely to produce more, whereas those with low RSE tend to produce less research output (Livinƫi et al, 2021;Nazari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%